Maggie and the Ferocious beast : the big scare - Paraskevas, Betty (New York : Simon & Schuster Books for Young Readers, 1999)
Maggie and Hamilton help their friend, the Ferocious Beast, when he confesses that he is afraid of mice.
Accelerated Reader AR
Keywords: Fear -- Fiction; Monsters -- Fiction; Mice -- Fiction; Pigs -- Fiction